THE ASSOCIATION BETWEEN MOTHERS' NUTRITIONAL KNOWLEDGE AND THE NUTRITIONAL STATUS OF CHILDREN UNDER FIVE AT SION CLINIC - Juliana Sion Sihombing; Nur Azizah Lubis; Andilala Andilala; Safriana; Afiatika Ahsani (Yayasan Amanah Nur Aman, 2026)
Children under five may experience adverse consequences from inadequate nutritional intake. Short-term effects include impaired brain development, intelligence, physical growth, and body metabolism, whereas long-term effects include reduced cognitive ability and academic achievement, weakened immunity, increased susceptibility to illness, and a higher risk of diabetes, obesity, cardiovascular disease, and health instability in later life. This study aimed to examine the association between mothers' nutritional knowledge and the nutritional status of children under five at Sion Clinic. A descriptive research design was employed. The population comprised all mothers with children under five in the Sion Clinic service area, while the sample consisted of 20 mothers whose children attended immunization services. Participants were selected through accidental (convenience) sampling, and data were collected using a questionnaire. Chi-square analysis yielded a p-value of 0.028, which was below the 0.05 significance level, indicating a statistically significant association between mothers' nutritional knowledge and children's nutritional status. Among the 20 respondents, six mothers (30%) had good knowledge and children with good nutritional status; three (15%) had good knowledge and children with adequate nutritional status; two (10%) had moderate knowledge and children with good nutritional status; five (25%) had moderate knowledge and children with adequate nutritional status; one (5%) had moderate knowledge and a child with poor nutritional status; one (5%) had poor knowledge and a child with adequate nutritional status; and two (10%) had poor knowledge and children with poor nutritional status. The findings indicate that higher maternal nutritional knowledge tends to be associated with better nutritional status among children under five. Maternal knowledge plays an important role in caregiving practices and the provision of appropriate nutrition for children.